2013
DOI: 10.1186/1472-6920-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous vs didactic education: it’s too early to throw in the towel on tradition

Abstract: BackgroundAsynchronous, computer based instruction is cost effective, allows self-directed pacing and review, and addresses preferences of millennial learners. Current research suggests there is no significant difference in learning compared to traditional classroom instruction. Data are limited for novice learners in emergency medicine. The objective of this study was to compare asynchronous, computer-based instruction with traditional didactics for senior medical students during a week-long intensive course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 16 publications
(18 reference statements)
1
70
1
2
Order By: Relevance
“…More research looking into ways to take advantage of the Generation Y learning style in our fast-growing environment of technology will be valuable. We may find that some areas of learning still require traditional methods [25].…”
Section: Some Modest Proposalsmentioning
confidence: 99%
“…More research looking into ways to take advantage of the Generation Y learning style in our fast-growing environment of technology will be valuable. We may find that some areas of learning still require traditional methods [25].…”
Section: Some Modest Proposalsmentioning
confidence: 99%
“…In the current study, we found that combining clinical learning with instructor-moderated case-based conferences improved learning outcomes. Novice learners may have unique needs and may not be able to extrapolate material they have read in a self-directed fashion, despite exposure to similar cases in the clinical setting, even with bedside teaching (19). It may be better to have an expert emphasize and explore content that has been seen in readings and the clinical setting with targeted small group didactics that allow for clarification of core concepts, applied in clinical situations, but without the pressure and interruptions that are inherent in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, computer-based teaching has gained momentum as an alternative, but it requires a substantial amount of resources, a complex plan of implementation as well as monitoring of the method. [12] Many research studies regarding recently introduced asynchronous, computer-based learning which claims to offer advantage of being flexible, student-centered and improved utilization of resources, have failed to find any significant advantage over traditional classroom-based teaching. [13,14] Hence, didactic lectures still remain popular mode of teaching.…”
Section: Discussionmentioning
confidence: 99%